Analysis of the morphometric characteristics of the Al-Shakrah valley Basin in the Western Plateau - Anbar Province (Journal of the College of Basic Education, 2024)
Al-Shukrah valley basin is one of the dry water basins that flow into the Euphrates River. The valley is located in the western plateau within the administrative borders of the Anbar Governorate and on the outskirts of the city of Al-Qaim. It occupies an area of ​​(205) km 2 and a length of 81 km. The study also relied on the analysis of quantitative morphometric characteristics (spatial, morphological, topography, and water drainage network) on data taken from topographical maps, satellite visuals, aerial images, and digital elevation data (DEM), From which it is concluded that the shape of the basin is far from the regular circular shape and its approach to the rectangular and triangular shape. This is due to the hard rock formations in the study area, represented by limestone rock. Either the results of the hyposometric integration, they were low and ranged between (0.22 and 1.10), that are indicating the valley basin is in the aging stage.